VALIDITAS LEMBAR KERJA SISWA BERBASIS PEDULI DAN BERBUDAYA LINGKUNGAN HIDUP DI SEKOLAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Izze Afkarina; Mamluatun Ni’mah; Wahyu Lestari (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to find out how the validity of learning tools in the form of student worksheets (LKS) based on caring and environmental culture in schools is oriented to problem solving and student curiosity. The research method used in this research is descriptive quantitative research that presents data from validators on the validity of LKS based on environmental care and culture in schools. The validator consists of two Mathematics Education experts. The instrument used is a validation sheet which shows that the worksheets meet the valid criteria for the very good category with an average validation score of 109. Based on the results of research and data analysis, it is concluded that the mathematics learning tools develop are categorized as very valid. However, it still needs to be tested practicality and effectiveness.